2023
DOI: 10.34133/research.0215
|View full text |Cite
|
Sign up to set email alerts
|

YAP Inactivation by Soft Mechanotransduction Relieves MAFG for Tumor Cell Dedifferentiation

Jiadi Lv,
Xiaohan Liu,
Yabo Zhou
et al.

Abstract: Solid tumor cells live in a highly dynamic mechanical microenvironment. How the extracellular-matrix-generated mechanotransduction regulates tumor cell development and differentiation remains an enigma. Here, we show that a low mechanical force generated from the soft matrix induces dedifferentiation of moderately stiff tumor cells to soft stem-cell-like cells. Mechanistically, integrin β8 was identified to transduce mechano-signaling to trigger tumor cell dedifferentiation by recruiting RhoGDI1 to inactivate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…To validate the resistance of cancer stem cells to NK cell attack, we performed cell sorting using a flow cytometer to separate CD133 + and CD133 − cell populations. According to previous studies [ 14 ], the 3D gel cell culture tumor sphere formation assay is a method used to assess the stemness of tumor cells. We found that CD133 + cells formed distinct clone spheres in the 3D gel, whereas CD133 − cells could not form noticeable tumor spheres (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the resistance of cancer stem cells to NK cell attack, we performed cell sorting using a flow cytometer to separate CD133 + and CD133 − cell populations. According to previous studies [ 14 ], the 3D gel cell culture tumor sphere formation assay is a method used to assess the stemness of tumor cells. We found that CD133 + cells formed distinct clone spheres in the 3D gel, whereas CD133 − cells could not form noticeable tumor spheres (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic force microscopy cell stiffness was measured according to standard methodology [ 13 , 14 ]. AFM force curves were captured with a customized Dimension Icon AFM (Bruker) placed atop an IX81 inverted optical microscope (Olympus) that had a heating stage for live‐cell imaging and a ×20 objective.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that modifying certain features, such as the ECM geometry [ 10 , 11 ], component, cell type, density, and pattern, significantly affects the physiological behavior of tissues and organs. For instance, alterations in ECM mechanical properties can affect cell proliferation, differentiation, and migration [ 12 14 ]. Differences in cell type or density can affect intercellular communication [ 15 17 ], while the arrangement of cells can affect the mechanical properties and regeneration growth of tissues [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%